Healthcare workers' attitudes towards working during pandemic influenza: A multi method study - Petts Judith; Parry Jayne; Greenfield Sheila; Gratus Christine; Ives Jonathan; Wilson Sue; Draper Heather; Sorell Tom (BMC, 2008)
Abstract Background Healthcare workers (HCWs) will be key players in any response to pandemic influenza, and will be in the front line of exposure to infection. Responding effectively to a pandemic relies on the majority of medical, nursing, laboratory and hotel services staff continuing to work normally. Planning assumes that during a pandemic normal healthcare service levels will be provided, although it anticipates that as caseloads increase only essential care will be provided. The ability of the NHS to provide expected service levels is entirely dependent upon HCWs continuing to work as normal. Methods/design This study is designed as a two-phase multi-method study, incorporating focus groups and a questionnaire survey. In phase one, qualitative methods will be used to collect the views of a purposive sample of HCWs, to determine the range of factors associated with their responses to the prospect of working through pandemic influenza. In phase two, the findings from the focus groups, combined with the available literature, will be used to inform the design of a survey to determine the generalisability of these factors, enabling the estimation of the likely proportion of HCWs affected by each factor, and how likely it is that they would be willing and/or able to continue to work during an influenza pandemic. Discussion There are potentially greater than normal health risks for some healthcare workers working during a pandemic, and these workers may be concerned about infecting family members/friends. HCWs will be as liable as other workers to care for sick family members and friends. It is vital to have information about how motivated HCWs will be to continue to work during such a crisis, and what factors might influence their decision to work/not to work. Through the identification and subsequent management of these factors it may be possible to implement strategies that will alleviate the concerns and fears of HCWs and remove potential barriers to working.